Impact of covid-19 pandemic on substance use - Sönmez, Doğancan; Sönmez, Kübra; Puşuroğlu, Meltem; Bahçeci, Bülent; Hocaoğlu, Çiçek (Journal of Dependence, 2025)
Objective: As the pandemic spreads worldwide, individuals are exposed to factors such as social isolation, economic uncertainty, and general stress, which has increased the risk of substance use and addiction. Studies show that the SARS-CoV-2 (COVID-19) pandemic has increased substance use disorders. The aim of this study is to examine the impact of the COVID-19 pandemic on substance use disorders. Method: The study was planned as a retrospective study. This study was based on March 11, 2020, the date when the COVID-19 case was first seen in Turkey, for 4 years, including two years before the pandemic and two years during the pandemic process, between 11.03.2018 and 11.03.2022. 1743 cases referred to the psychiatric outpatient clinic within the scope of probation were included. Results: While substance use was detected in 834 people in the pre-COVID-19 pandemic period (March 2018-March 2020), substance use was detected in 909 people during the COVID-19 pandemic period (March 2020-March 2022). A significant increase in substance use was detected in female gender during the pandemic period. A statistically significant increase was observed in methamphetamine, opioid, cocaine and multiple substance use during the pandemic period compared to the pre-pandemic period. Conclusion: The data of our study show substance use rates in Turkey before and during the pandemic. The study will be useful to understand the impact of COVID-19 on drug use frequencies in Türkiye.